Effectiveness of Education based on Orem's Self-Care Model in Self-Care Activity of Patients with Implantable Cardioverter Defibrillators - Khodayar Oshvandi; Khodadad Keshmiri; Mohsen Salavati; Zahra Emkanjoo; Saeid Musavi (Tehran University of Medical Sciences, 2014)
Background & Aim: Several studies have shown that the self-care activity of patients with implantable cardioverter defibrillator is inadequate. This study was conducted to assess the effect of an educational program based on the Orem's self-care model in self-care ability of the patients .   Methods & Materials: This clinical trial was conducted among 66 patients with implantable cardioverter defibrillator. Four educational sessions were held based on the patient's needs and Orem's self-care model. Data was collected using a self-report questionnaire at baseline and one month after the intervention. Data were analyzed using statistical tests (x2, t-test, paired t-test) in the SPSS-18 .   Results: There were no significant differences in the self-care awareness, tendency to self-care, self-care skills, and self-care ability between the control and intervention groups. After the intervention, the self-care awareness score remained 22.06 ± 3.26 in the control group and increased (28.69 ± 1.51) in the intervention group (P<0.000). There was also significant difference in the tendency to self-care between the control (25 ± 3.31) and intervention (28.9 ± 1.33) groups (P<0.000). The self-care skills differed significantly between the control (14.9±3.06) and intervention (29.03±1.15) groups after the intervention (P<0.000). After the intervention, the self-care ability was also significantly different among the control (61.96±8.06) and intervention (86.63±2.93) groups (P<0.000) .   Conclusion: The results of this study showed that implementing educational programs based on the Orem's self-care model can improve self-care ability in patients with implantable cardioverter defibrillator. Applying this method is recommended in nursing interventions to promote health status of the patients .